2010
DOI: 10.1158/1940-6207.capr-09-0243
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effects of Salvianolic Acid B with Low-Dose Celecoxib on Inhibition of Head and Neck Squamous Cell Carcinoma Growth In vitro and In vivo

Abstract: Head and neck squamous cell carcinoma (HNSCC) development is closely associated with inflammation. Cyclooxygenase-2 (COX-2) is an important mediator of inflammation. Therefore, celecoxib, a selective inhibitor of COX-2, was hailed as a promising chemopreventive agent for HNSCC. Dose-dependent cardiac toxicity limits long-term use of celecoxib, but it seems likely that this may be diminished by lowering its dose. We found that salvianolic acid B (Sal-B), isolated from Salvia miltiorrhiza Bge, can effectively su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 44 publications
1
60
0
2
Order By: Relevance
“…NSAIDs could suppress COX-2 expression and prevent the effects of prostaglandins. Celecoxib, the first selective COX-2 inhibitor approved by the U.S. Food and Drug Administration, has been reported to prevent carcinogenesis in both animals and humans [11,12,13]. Moreover, it has been reported that the chemotherapy, including celecoxib when used at low dose, may be able to enhance the efficacy of radiation treatment on the cancer cells [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs could suppress COX-2 expression and prevent the effects of prostaglandins. Celecoxib, the first selective COX-2 inhibitor approved by the U.S. Food and Drug Administration, has been reported to prevent carcinogenesis in both animals and humans [11,12,13]. Moreover, it has been reported that the chemotherapy, including celecoxib when used at low dose, may be able to enhance the efficacy of radiation treatment on the cancer cells [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Utvrđeno je da Sal B dostiže maksimum koncentracija u plazmi već 0,5-1 sat nakon oralne primene i njeni metaboliti mogu biti prisutni u organizmu i nakon 180 minuta od trenutka primene (17). U dosadašnjim studijama glavni zabeleženi efekti Sal B jesu kardioprotektivna, neuroprotektivna i antitumorska svojstva, zasnovana pre svega na njenom antioksidativnom potencijalu (17,18,32,33,34). Pokazano je da Sal B štiti ćelije endotela, arterijske glatke mišićne ćelije i kardiomiocite od slobodnih radikala i peroksidacije, tako što redukuje intracelularni oksidativni stres (17).…”
Section: Diskusijaunclassified
“…Salvianolična kiselina B ima jako hemopreventivno dejstvo koje ostvaruje najverovatnije pomoću antioksidativnih i antiinflamatornih mehanizama. Naime, pretpostavlja se da je modulacija apoptoze preko vodonik-peroksida jedan od glavnih puteva za suzbijanje rasta ćelija kancera (32,34). Do sada nisu zabeleženi efekti Sal B na integritet jedarne DNK pomoću alkalnog Komet testa i ova studija je po prvi put prikazala odsustvo genotoksičnosti i antigenotoksični potencijal Sal B.…”
Section: Diskusijaunclassified
“…11 Apart from anti-inflammation, anticoagulation, and antioxidation, Sal B has also shown obvious anticancer activity in a variety of cancer cell lines, including prostate, breast, liver, and head and neck squamous cell cancers. [12][13][14] Curcumin (Cur) is diferuloylmethane or 1,7-bis(4-hydroxy-3-methoxyphenyl)-1,6-hepadiene-3,5-dione, and has presented a comprehensive array of pharmacological properties, such as anti-inflammatory, antioxidant, anticancer, antimicrobial, antiparasitic, antitumor, antiangiogenic, and antimutagenic effects. 15 Currently, Cur is used mainly for inhibiting cancer in a variety of cell lines, and has expressed obvious antitumor effects, eg, in breast cancer and ovarian cancer.…”
Section: Ding Et Almentioning
confidence: 99%